Effectiveness of educational videos on communication skills to enhance adolescents' knowledge for preventing child marriage - Nenden Rani Rinekasari; Elih Sudiapermana; Sardin Sardin; Yoyoh Jubaedah (Inovasi Kurikulum, 2025)
Child marriage remains a critical issue in Indonesia, particularly among adolescents aged 12 to 15 years who are vulnerable due to psychological immaturity and environmental influences. Strengthening adolescents' knowledge and communication skills is crucial in preventing early marriage. This study aims to evaluate the effectiveness of educational videos in enhancing adolescents' knowledge of child marriage prevention by improving their communication skills. Employing a quasi-experimental one-group pre-test-post-test design, the study involved 32 students of class VII-F at SMP Negeri 27 Bandung. Data were collected through pre-test and post-test assessments, using multiple-choice tests administered before and after the intervention. The data were analyzed using the Wilcoxon signed-rank test to determine the significance of differences between pre-test and post-test scores, and the N-Gain calculation was employed to assess the effectiveness of the intervention. The findings demonstrated a statistically significant increase in knowledge after the intervention, with an average N-Gain score of 0.5690, indicating moderate effectiveness. Improvements were observed in critical communication skills, including speaking, listening, overcoming verbal barriers, understanding nonverbal cues, and conflict resolution. Educational videos effectively enhance communication skills and knowledge about child marriage prevention among adolescents.   Abstrak Pernikahan anak tetap menjadi masalah kritis di Indonesia, terutama di kalangan remaja berusia 12 hingga 15 tahun yang rentan akibat ketidakmatangan psikologis dan pengaruh lingkungan. Peningkatan pengetahuan dan keterampilan komunikasi remaja sangat penting untuk mencegah pernikahan dini. Studi ini bertujuan untuk mengevaluasi efektivitas video edukatif tentang keterampilan komunikasi dalam meningkatkan pengetahuan remaja mengenai pencegahan pernikahan anak. Menggunakan desain quasi-eksperimental satu kelompok pre-tes dan post-tes, penelitian ini melibatkan 32 siswa kelas VII-F di SMP Negeri 27 Bandung. Data dikumpulkan melalui penilaian pre-tes dan post-tes, menggunakan tes pilihan ganda yang diberikan sebelum dan setelah intervensi. Data dianalisis menggunakan uji Wilcoxon signed-rank untuk menentukan signifikansi perbedaan antara skor pre-tes dan post-tes, dan perhitungan N-Gain digunakan untuk mengukur efektivitas intervensi. Temuan menunjukkan peningkatan yang signifikan secara statistik dalam pengetahuan setelah intervensi, dengan skor N-Gain rata-rata 0,5690, menunjukkan efektivitas moderat. Peningkatan diamati pada keterampilan komunikasi kritis, termasuk berbicara, mendengarkan, mengatasi hambatan verbal, memahami isyarat nonverbal, dan penyelesaian konflik. Video pendidikan secara efektif meningkatkan keterampilan komunikasi dan pengetahuan tentang pencegahan pernikahan anak di kalangan remaja. Kata Kunci: keterampilan komunikasi; pencegahan pernikahan anak; peningkatan pengetahuan; video edukasi